PIM recommendations and capacity building and outreach efforts contribute to the reform of the Agricultural Research Council of Nigeria towards improved efficiency, impact and sustainability of agricultural research - CGIAR Research Program on Policies, Institutions, and Markets (2021)
PIM recommendations, capacity building and outreach efforts have contributed to the Agricultural Research Council of Nigeria Amendment Act, which was passed into law in October 2021. This first milestone on the road to reforming ARCN towards improved efficiency, impact and sustainability of agricultural research is the result of a longstanding partnership between IFPRI's Nigeria Strategy Support Program and ARCN, with support from PIM. IFPRI has also been requested to support the implementation of the reform.